ANALISIS INTENSITAS PETIR CLOUDE TO GROUND (CG) DI WILAYAH PROVINSI SUMATERA UTARA TAHUN 2022 - Ramadan, Tengku Surya; Lubis, Lailatul Husna; Sari, Novita (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2024)
Lightning is air electricity that occurs due to the discharge of electric charges from clouds in the form of negatively and positively charged electricity which usually occurs in convective clouds. can damage and harm humans. This study aims to analyze the intensity of lightning strikes (CG) in the North Sumatra region in 2022 and relate lightning strikes to rainfall. The research method used is a quantitative method by utilizing ArcGIS 10.8 software using the kriging method as an interpolation for mapping the density of the number of lightning strikes in each Regency/City. The data used is real-time data all day long in the form of a database recorded by Lightning Detector for one year. The results of this research are the areas with the highest number of lightning strikes occurring in Deli Serdang Regency with 345168 lightning strikes with a lightning density of >300 strikes strikes per square kilometer. and the area with the lowest number of strikes was Sibolga district with a total of 34 lightning strikes in a year (CG) with a lightning strike density of <100 strikes per square kilometer.